Invader's portrait: Biological characteristics of walleye pollock Gadus chalcogrammus in the western Chukchi Sea - Emelin, Pavel O.; Maznikova, Olga A.; Benzik, Alexander N.; Sheibak, Artem Yu; Trofimova, Anastasiya O.; Orlov, Alexei M. 1960- (Deep sea research. Part II: Topical studies in oceanography)
Presented here are data on the size composition and age structure, the sex ratio, the state of maturity of the gonads, and the composition of the diet and feeding habits of walleye pollock in the western Chukchi Sea, based on 2003-2020 bottom and mid-water trawl surveys conducted onboard Russian research vessels. During all years of research, mid-water trawl catches in this area were dominated by juveniles with FL 5-12 cm, while the size composition of walleye pollock in bottom trawl catches was bimodal with the dominance of fish 7-14 cm and 50-62 cm long. Females were considerably larger than males (on average by almost 10 cm), with mean FL 56.0-58.3 cm and 52.1-56.4 cm, respectively, in different years. The age structure of walleye pollock was significantly different from that of both the western and eastern Bering Sea since fingerlings and yearlings predominated there in the mid-water trawl catches, and fish under the age of 1 year and 6-17 years were the most numerous in the bottom trawl catches. In the western Chukchi Sea in 2018-2020, the proportion of females in bottom trawl catches ranged from 1.8 to 2.7 females per male. This is probably because walleye pollock here were represented mainly by large fish, while in the mature part of the population, females are usually larger than males. The proportion of fish with gonads at different stages of maturity varied significantly in different years. Immature individuals were extremely few among the fish analyzed. Individuals with developing and postspawning gonads accounted for a major part of the catches. In recent years, walleye pollock of both sexes have been observed in pre-spawning, spawning, and post-spawning condition, which may indicate the possibility of spawning of individual specimens in the western Chukchi Sea. The survival of eggs, larvae, and fry in conditions of low temperatures is unlikely. However, if the warming in the Arctic continues, it is possible that new walleye pollock spawning grounds may appear in the Chukchi Sea. In the western Chukchi Sea, the proportion of euphausiids in the diet of large walleye pollock (>40 cm in 2018 and > 60 cm in 2019) was significantly higher than that of small fish (<40 cm). In the average long-term plan, the decrease in its diet with the growth was characteristic only for planktonic organisms (small crustaceans, chaetognaths, and larvaceans). Only large benthic crustaceans showed an increase in the walleye pollock diet as it grew. There were no pronounced trends regarding euphausiids and fish. In the western Chukchi Sea, the cannibalism was registered only in large individuals (40-60 cm and >60 cm) and only in 2019 with small number juveniles consumed. Such a low level of cannibalism was probably due to the spatial separation of juveniles and adults, as well as the presence of a sufficient amount of other prey.